(untitled) (American Journal of Islam and Society, 2005)
In medieval Islamic civilization, poetry was widely acknowledged to be the most intimate vessel for conveying Sufism’s hidden truths. The spiritual states and stations traversed by adepts along an ascending path to the reality of God’s unity largely defies simple descriptions into ordinary prose or everyday language. The subtleties necessary to evocatively describe a spiritual journey that is, by its very essence, ineffable, necessitates a linguistic medium that could at once reveal secrets of inner contemplation and mystical perception while simultaneously concealing such information from the “uninitiated” behind the exoteric understanding of the same work of literature. Persian poetry, with its unique capacity for metaphorical symbolism, puns, and paradoxes, thus emerged by the seventh/thirteenth century as an unparalleled vehicle for expressing the mystical experience. The most dramatic expression in all of Persian mystical literature of this spiritual journey is the allegorical poem Mantiq al-Tair (best translated as “The Speech of the Birds”) by Farid al-Din `Attar (d. 627/1229), which recounts the initiatory voyage of a group of birds through seven valleys to the palace of the mythical king-bird Simurgh, symbol of the Divine, enthroned atop the cosmic mountain Qaf. In addition to the book currently under review, `Attar’s masterpiece inspired other renditions into English, including an abbreviated and freely reworked edition by Edward FitzGerald, The Bird-parliament (1903); R. P. Masani’s prose translation of half the original poem’s 4,600 lines, The Conference of the Birds (1924); the incomplete prose version by C. S. Nott, The Conference of the Birds (1954), which was prepared from Garcin de Tassy’s nineteenth-century French translation, Le Langage des oiseaux, and, as such, is obscured by an intervening third language; Afkham Darbandi and Dick Davis’ Penguin Classics edition The Conference of the Birds (1984), which represents the poem’s first complete English translation (minus the invocation and epilogue), is based on the oldest extant manuscripts, and is skillfully rendered into heroic couplets pleasingly faithful to the letter and spirit of `Attar’s allegory; and Peter Avery’s determinedly literal translation, The Speech of the Birds (1998), whose 560-page opus includes 120 pages of enriching endnotes on `Attar’s use of Qur’anic imagery and the hadith ...